Determinants of Anemia Among Pregnant Women Attending in a Tertiary Level Hospital, Kathmandu - Mulepati, Sumitra; Chaudhary, Tanuja Kumari (Med Phoenix, 2017)
Background: Anemia is a common problem in pregnancy, particularly in developing countries which causes low birth weight and increased risk of maternal and perinatal morbidity and mortality. Methods: A descriptive cross-sectional study was adopted to determine the factors associated with anemia among pregnant Systematic Random Sampling technique was used and sample size was 280 pregnant women who visited the antenatal clinic of the Tribhuwan University Teaching Hospital, Kathmandu. Data was collected by face to face interview technique by pretested questionnaire. Chi-square, bivariate, multivariate logistic regression model was used, and statistical significance was determined with a 95% confidence level. Results: Mean age of respondents was 25.86±4.191 years. Anemia among pregnant women was 22.1%.The significant determinants associated with anemia were pregnant women who had not taken iron regularly (AOR=18.380, 95% CI=3.687-91.624, p=0.005). Conclusion: The results indicate that anemia is still prevalence in pregnant women in tertiary level hospital at Kathmandu. Irregular intake or discontinuation of iron was significant factor for anemia. Therefore, pregnant women and their family members need counseling about the importance of regular intake of iron during pregnancy. Med Phoenix Vol.2(1) July 2017, 24-33